Anti-Alzheimer’s Activity of Compounds from the Methanolic Extract of Lawsonia inermis Seeds: In vivo and in silico Molecular Docking Studies - Jyothi, Punabaka; Yellamma, Kuna (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Alzheimer's disease (AD) hallmark feature is neurodegeneration due to the accumulation of β-amyloid plaques and the formation of neurofibrillary tangles in the aged brain. The prevalence of AD in humans is doubled for every two decades and is expected to reach 74.7 million worldwide by 2030. Numerous treatment approaches for AD are currently available but success rate is very limited, therefore novel medicines that minimize AD progression are urgently needed. Methods: In this study, in vivo experiments were performed to test the anti-Alzheimer’s property of MELIS on male albino rats under D-galactose induced AD. Estimation of ACh content and AChE activity in cerebral cortex was done in different groups of rats. In addition, in in silico analysis, molecular docking of MELIS compounds against AChE was performed in Auto dock vina software tool. Results: MELIS exhibited Anti-alzheimer’s properties in rats by modulating ACh and AChE. Further, in silico molecular docking studies found top 10 MELIS compounds such as Dihydromyricetin, Quercitrin, Zearalenone, Leupeptin, Moricizinesulfone, Lecanoric acid, Sulfamerazine, 3-Deoxyguanosine, N-(3-indolylacetyl)-lisoleucine and Trimethoprim exhibited anti-acetylcholinesterase (AChE) property through showing good binding affinity by forming hydrogen bond interactions with active site amino acids. Conclusion: It is conclude from the results that MELIS compounds exhibit anti-Alzheimer property by modulating the ACh content, AChE activity and interacting to AChE active site amino acids. Therefore MELIS could be preferred source of active compounds for isolation and identification of new drugs for the AD treatment
Keywords: Alzheimer’s Disease; AChE; ACh; Cholinergic systems; Docking studies and; Lawsonia inermis